Toxicity Effect Test of Matoa (Pometia pinnata) Plant Fractions as Raw Materials for Anticancer Drugs: Uji Efek Toksisitas Fraksi Tanaman Matoa (Pometia pinnata) Sebagai Bahan Baku Obat Antikanker - Hasan, Hamsidar; Taupik, Muhammad; Ihsan, Muh.; Andi Suryadi, A. Mu’thi (Universitas Tadulako, 2024)
Background:The prevalence of cancer in Indonesia increases every year. Medical treatments such as chemotherapy, surgery, and radiation require significant costs with considerable side effects. Therefore, there is a need for chemopreventive agents from natural sources such as plants. One plant with potential as a chemopreventive agent is the matoa tree (Pometia pinnata), which is empirically used to treat suppurating wounds.Objectives: This research aims to test the toxicity of leaf and stem bark fractions of matoa using shrimp larvae Artemia salina Leach. Methods: The parameter for this study is the LC50 value. The extraction method involves successive maceration using solvents based on increasing polarity, starting with n-hexane, chloroform, ethyl acetate, and methanol. Phytochemical screening is conducted using colour tests, and toxicity is assessed through the brine shrimp lethality test. The research indicates that all fractions of matoa leaves and stem bark are toxic with respective LC50 values for leaf fractions: n-hexane (394.8 µg/mL), chloroform (244.3 µg/mL), ethyl acetate (180.6 µg/mL), and methanol (303.2 µg/mL). Stem bark fractions exhibit LC50 values in the order of n-hexane (203.9 µg/mL), chloroform (244.3 µg/mL), ethyl acetate (144.8 µg/mL), and methanol (58.3 µg/mL). Conclusions: All fractions fall into the toxic category and have the potential as raw materials for anti-cancer drugs.